1994
DOI: 10.1161/01.str.25.8.1644
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vasodilation of cerebral vessels induced by the potassium channel opener nicorandil in canine in vivo experiments.

Abstract: Nicorandil, a potent antianginal agent characterized as a potassium channel opener, could produce cerebrovascular dilation in in vitro studies. Our aim was to investigate the pharmacologic response to the topical application of nicorandil on the vasomotor tone of pial vessels in vivo. To elucidate its mechanism, we also studied the inhibitory action of methylene blue and glibenclamide against nicorandil-induced vasodilation. In 14 dogs prepared with a parietal cranial window, we administered five dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…11 K-channels contribute to membrane potential in cerebral vessels. [12][13] Our hypothesis in this study was that hyperthermia inhibits K channels in smooth muscle cells of the carotid arteries, causing depolarization and vasoconstriction.…”
Section: Discussionmentioning
confidence: 96%
“…11 K-channels contribute to membrane potential in cerebral vessels. [12][13] Our hypothesis in this study was that hyperthermia inhibits K channels in smooth muscle cells of the carotid arteries, causing depolarization and vasoconstriction.…”
Section: Discussionmentioning
confidence: 96%
“…22,23 The opening of such channels in the vascular smooth muscle cell causes vasorelaxation. 24 The complete inhibition of smokinginduced pial vasodilation by glibenclamide, a putative ATPsensitive K ϩ channel blocker, 25 suggests that this response is probably induced via an activation of ATP-sensitive K ϩ channels in the cerebral arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…25 Indeed, we have previously demonstrated that topical application of glibenclamide can effectively block cromakalim-induced pial arteriolar and venular dilation in the dog in vivo. 22 In rat studies, the following occurred: (1) 20 mg/kg of glibenclamide given intravenously blunted the vasodilator effect of the K ϩ channel opener, diazoxide, but not that of the L-type Ca 2ϩ channel blocker, nicardipine, 26 and (2) 20 to 30 mg/kg of glibenclamide given intravenously inhibited the vasorelaxant Propranolol 132Ϯ4 136Ϯ7 145Ϯ10 151Ϯ10 134Ϯ5 124Ϯ12 124Ϯ8 128Ϯ5 129Ϯ4 125Ϯ3 L-NAME 125Ϯ5* 142Ϯ8 152Ϯ11 157Ϯ12 † 146Ϯ9 137Ϯ8 136Ϯ7 138Ϯ5 138Ϯ5 146Ϯ6 Glibenclamide 121Ϯ8 132Ϯ6 137Ϯ6 142Ϯ9* 135Ϯ6 133Ϯ5 132Ϯ5 129Ϯ4 129Ϯ4 127Ϯ5 Seratrodast 118Ϯ5 125Ϯ5 143Ϯ5* 163Ϯ5 † 128Ϯ5 124Ϯ5 124Ϯ5 127Ϯ5 126Ϯ4 122Ϯ5 HR, bpm…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Pial arterioles are important because they reflect cerebral blood flow. [5][6][7][8] Pial arterioles are important because they reflect cerebral blood flow.…”
mentioning
confidence: 99%